2006
DOI: 10.1111/j.1439-0523.2006.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal substitutions analysis of freezing resistance in wheat (Triticum aestivum L.)

Abstract: To investigate the effects of individual chromosomes on freezing resistance, as well as their interactions with the genetic background, reciprocal sets of chromosome substitution lines between two hard red winter wheat cultivars, ÔCheyenneÕ and ÔWichitaÕ, were used in this study. Duplicate lines for each chromosome were included to check background homogeneity. Two experiments were carried out in complete block designs with two replications for each duplicate. Crown and leaf water content and leaf wet weight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…The results indicate that five ‘Bez’ chromosomes (5A, 2D, 4A, 5D and 6A) participate in the plant defence system against low temperature stress. These confirm the effects of chromosomes 5A and 5D on frost tolerance, reported by other authors (Veisz and Sutka 1989, Sutka and Snape 1989, Galiba et al 1995, Snape et al 1997, Sutka et al 1999, Sutka 2001, Danyluk et al 2003, Tóth et al 2003, Yazdi‐Samadi et al 2006). Because the 5BL‐7BL substitution line was unavailable, it was not possible to test whether the frost‐resistant gene Fr‐B1 known to be located on the 5BL arm was present in ‘Bez’.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicate that five ‘Bez’ chromosomes (5A, 2D, 4A, 5D and 6A) participate in the plant defence system against low temperature stress. These confirm the effects of chromosomes 5A and 5D on frost tolerance, reported by other authors (Veisz and Sutka 1989, Sutka and Snape 1989, Galiba et al 1995, Snape et al 1997, Sutka et al 1999, Sutka 2001, Danyluk et al 2003, Tóth et al 2003, Yazdi‐Samadi et al 2006). Because the 5BL‐7BL substitution line was unavailable, it was not possible to test whether the frost‐resistant gene Fr‐B1 known to be located on the 5BL arm was present in ‘Bez’.…”
Section: Discussionsupporting
confidence: 91%
“…We assume that the stronger survivability among the plants of the ÔBezÕ variety was also caused by genes, expressed under lower temperatures of hardening. The observed effect of the substitution of chromosome 6A agrees with the earlier results of Bo¨rner et al (2001) who reported a low temperature stress tolerance gene located on chromosome 6A tightly linked to the Xfba85-6A and Xpsr10 (Gli-2)-6A loci, though substitution of 6A along with chromosomes 3B and 5D of variety ÔCheyenneÕ by the homologous ones of ÔWichitaÕ decreased freezing resistance (Yazdi-Samadi et al 2006). The plant survival during the winter period is determined by the extent and duration of the expression of frost tolerance genes (Fowler et al , 1999.…”
Section: Discussionsupporting
confidence: 90%
“…The conductivity was again measured and damage due to freezing was expressed as the ratio of the conductivity before freezing in liquid nitrogen to conductivity after freezing in liquid nitrogen. Others have shown that these kinds of electrolyte leakage measurements following freezing can be used to predict freezing tolerance of wheat plants (Khanna & Daggard, ; Sun, Hu, Tan, Liu, & Liu, ; Yazdi‐Samadi, Dashti, Nabipour, & Sarrafi, ).…”
Section: Methodsmentioning
confidence: 99%
“…Others have shown that these kinds of electrolyte leakage measurements following freezing can be used to predict freezing tolerance of wheat plants (Khanna & Daggard, 2006;Sun, Hu, Tan, Liu, & Liu, 2009;Yazdi-Samadi, Dashti, Nabipour, & Sarrafi, 2006).…”
Section: Plant Materials and Freeze Damage Assessmentsmentioning
confidence: 99%